Coevolution of minerals in lacustrine mudstone during diagenesis: a case study of the dongying depression in the Bohai Bay Basin - Zhang, Zongxuan; Jiang, Zaixing; Yang, Yepeng (Frontiers in Earth Science, 2025)
In sedimentary basins, the lithologic characteristics of mudstone in different lithofacies differ, which is caused by the different types of diagenesis after sedimentation. An accurate understanding of the changes in and interactions among minerals in mudstone during diagenesis plays a key role in shale oil and gas exploration and development. In this work, the petrologic characteristics, XRD data, carbon and oxygen isotope data, main trace element data, and rock pyrolysis data of a total of 137 samples from 3 wells were used to divide the studied mudstone into 5 different types of lithofacies. For each rock phase and all kinds of primary minerals, the changes in secondary minerals and the relationships among them were studied. The five types of lithofacies belong to a relatively closed diagenetic system. The main development space of fibrous calcite/ankerite is laminar fractures formed during the sedimentary period. Ca2+, Mg2+ and Fe2+ ions are provided by early carbonate and smectite–illite transformation. According to the temperature calculated from the δ18O values, the formation time of fibrous calcite/ankerite is the same as that of organic acid production. A large amount of fine quartz is formed by the transformation of clay minerals, and SiO2 precipitation is formed by the dissolution of terrigenous feldspar. The authigenic albite precipitates in carbonate dissolution pores when the production of organic acids is reduced. Authigenic carbonate affects the smectite‒illite transformation process by influencing the ion concentration in the pore fluid. Pyrite transforms from colloidal pyrite formed by the action of BSR in the early stage of diagenesis and affects the concentration of Fe2+ ions in the early pore fluid. The contents and types of organic matter in different lithofacies differ, which directly leads to differences in pore fluid pressure and organic acid concentration during the thermal evolution stage of organic matter, thus affecting the diagenesis of different lithofacies.